2011
DOI: 10.1093/scan/nsr059
|View full text |Cite
|
Sign up to set email alerts
|

Personality modulates the effects of emotional arousal and valence on brain activation

Abstract: The influence of personality on the neural correlates of emotional processing is still not well characterized. We investigated the relationship between extraversion and neuroticism and emotional perception using functional magnetic resonance imaging (fMRI) in a group of 23 young, healthy women. Using a parametric modulation approach, we examined how the blood oxygenation level dependent (BOLD) signal varied with the participants' ratings of arousal and valence, and whether levels of extraversion and neuroticis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 95 publications
9
57
1
3
Order By: Relevance
“…The young cohort is the same as those described in Kehoe et al (2011); however this study additionally contains data from an older cohort and concentrates on aging differences. The groups did not differ in their educational attainment (t ϭ 1.15, p Ͼ 0.05).…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…The young cohort is the same as those described in Kehoe et al (2011); however this study additionally contains data from an older cohort and concentrates on aging differences. The groups did not differ in their educational attainment (t ϭ 1.15, p Ͼ 0.05).…”
Section: Participantsmentioning
confidence: 99%
“…Previous studies have found that neuroticism can influence the neural substrates of emotional processing (Canli et al, 2001;Haas et al, 2008;Kehoe et al, 2011), leading to sustained processing of sad stimuli for example (Haas et al, 2008), and increased activation in response to arousal in the mPFC (Kehoe et al, 2011). Therefore in order to control for the possible confounding effect of this trait it was included as a covariate of no interest in all of the fMRI analyses.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations